Faktor Hambatan Penyidikan Dalam Kasus Tindak Pidana Cybercrime - Dani Septian Nugroho; Margo Hadi Pura (Jurnal Program Pascasarjana Ilmu Hukum Universitas Islam As-Syafi'iyah, 2022)
Investiagtion is a process of a investigate to found evidence, suspect and resolve the criminal case, but in the reality there’s a obstacle during investigation. For example is on decision letter Number 1206/Pid.Sus/2019/PN.Jkt.Brt. The problem in this journal is kinds of causes factor obstacle happen. This research is intended to find out in depth the factors of investigation conspiracy. In this research is using method of juridical-normative approach, namely analyzing Law Number 11 of 2008, PN Jkt Brt Decision, and literature or books as a type of secondary data related to investigation conspiracy. The results showed that one of the factors that caused the investigation carried out by several problem and obstacle, and causes there’s a 4 case on 1 suspect then involved 1 linguist, for other factors will be explained more broadly in the discussion of this journal. Keywords : Factors; Investigation; Cybercrime